Alcohol and moral regulation : public attitudes, spirited measures and Victorian hangovers - Yeomans, Henry (Policy Press, 2014)
Alcohol consumption is frequently described as a contemporary, worsening and peculiarly British social problem that requires radical remedial regulation. Informed by historical research and sociological analysis, this book takes an innovative and refreshing look at how public attitudes and the regulation of alcohol have developed through time. It argues that, rather than a response to trends in consumption or harm, ongoing anxieties about alcohol are best understood as 'hangovers' derived, in particular, from the Victorian period. The product of several years of research, this book aims to help readers re-evaluate their understandings of drinking. As such, it is essential reading for students, academics and anyone with a serious interest in Britain's 'drink problem'.